THE IMPACT OF SAFETY AND HEALTH ISSUES ON THE CONSTRUCTION WORKFORCE PRODUCTIVITY IN MALAYSIA - Wong, Queenie (2023)
This research aims to study the impact of safety and health of the construction workforce productivity among workers in G3 contractors in Kuantan, Pahang, Malaysia. Previous research found that construction companies face a lack of safety concerns due to insufficient safety compliance and poor attitude towards safety. While poor safety measures in the working environment and material storage cause injuries and accidents that affect work on-site. Lack of health concerns based on physical and mental health issues affected the productivity of the construction workers. In this study, a quantitative research is used to collect and analyze data using the PLS-SEM model. This research has collected 152 responses from workers of G3 contractors in Kuantan, Pahang. Hence, the result of this study could be used as a reference for future studies among the constructions companies in improving the productivity of their workers in order to sustain their business operation.